Reduced antibody response to COVID-19 vaccine composed of inactivated SARS-CoV-2 in diabetic individuals - Cheng, Yandong; Shen, Ping; Tao, Yue; Zhang, Wenjun; Xu, Biyun; Bi, Yan; Han, Zhen; Zhou, Yi-Hua (Frontiers in Public Health, 2022)
Background: Patients with type 2 diabetes mellitus (T2DM) are at increased risk for COVID-19 related morbidity and mortality. Antibody response to COVID-19 vaccine in T2DM patients is not very clear. The present work aims to evaluate the antibody response to the inactivated SARS-CoV-2 vaccine in this population. Methods: Two groups of subjects with no history of SARS-CoV-2 infection were included: 63 T2DM patients and 56 non-T2DM controls. Each participant received two doses of inactivated COVID-19 vaccine. IgG antibodies against the nucleocapsid (N) and spike (S) proteins of SARS-CoV-2 (anti-N/S IgG) and receptor binding domain (RBD) proteins (anti-RBD IgG) were quantitatively evaluated by the electrochemiluminescence immunoassays respectively. Results: It was observed that the positive rates and titers of anti-N/S IgG and anti-RBD IgG in T2DM patients were significantly lower than those in controls respectively (anti-N/S: 85.7% vs 98.2%, P = 0.034; 25.48 vs 33.58 AU/ml P = 0.011; anti-RBD: 85.7% vs 96.4%, P = 0.044; 15.45 vs 22.25 AU/ml, P = 0.019). Compared to non-T2DM subjects, T2DM patients with uncontrolled glycemia showed lower positive antibody rates and titers (anti-N/S IgG: 75% and 13.30 AU/ml; anti-RBD IgG: 75% and 11.91 AU/ml, respectively, all P<0.05), while T2DM patients with controlled glycemia had similar positive antibody rates and titers (anti-N/S IgG: 94.3% and 33.65 AU/ml; and anti-RBD IgG: 94.3% and 19.82 AU/ml, respectively, all P >0.05). Conclusion: In the analysis performed, the data indicate that T2DM patients with uncontrolled glycemia showed a lower level of IgG antibodies compared to non-diabetic controls and individuals with controlled glycemia when immunized with the inactivated COVID-19 vaccine.